2010
DOI: 10.1007/s10549-010-1140-4
|View full text |Cite
|
Sign up to set email alerts
|

Fertility drugs and the risk of breast cancer: a meta-analysis and review

Abstract: The risk of breast cancer has been associated with reproductive history. The purpose of this study was to determine the relationship between fertility drugs used in assisted reproductive procedures and the risk of breast cancer. We performed a literature search using the MEDLINE, the COCHRANE Library, and Scopus to identify studies linking breast cancer to fertility drugs. We excluded case series, case reports, and review articles from our analysis. The study populations included women who were treated for inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Clomiphene citrate is a non-steroidal, selective ER modulator with both agonistic and antagonistic activity; it is widely used for ovulation induction in women with anovulatory causes of infertility (Klip et al, 2000). Several studies have pointed toward an association between clomiphene citrate exposure and breast cancer risk, and while a recent meta-analysis did not confirm this finding, this result was hampered by the lack of long-term follow-up for the majority of available studies used to power the analysis (Zreik et al, 2010). Clomiphene citrate binds ER at multiple locations in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, invasive BRCA1 breast tumors are often high grade and rapidly growing [33,34]. While a possible linkage between IVF treatment and breast cancer risk has extensively been studied in the general population [35], safety of IVF with regards to the risk for breast cancer has not been systematically studied in female BRCA1/2 carriers. Gonadotropin use for IVF results in a rise in estrogens.…”
Section: Discussionmentioning
confidence: 99%